2018
DOI: 10.7150/jca.27015
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of Cyclin-Dependent Kinase 5 and Protein Phosphatase 2A in Gastric Cancer

Abstract: Purpose To discuss the relationship between the clinicopathological data, long-term survival of gastric cancer patients and different expression levels of Cyclin-Dependent Kinase 5 (CDK5) and Protein Phosphatase 2A (PP2A).Method The expression levels of CDK5 and PP2A were detected by immunohistochemistry in specimens from 124 patients with primary gastric cancer. The correlation among the expression of CDK5 and PP2A, clinicopathological factors and prognosis was investigated.Result The expression level of CDK5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We found that TIE1 was upregulated in human cervical cancer and correlated with a poor prognosis. Consistent with our results, it has been indicated that elevated TIE1 expression is associated with a poor prognosis in patients with gastric cancer, ovarian cancer and metastatic breast cancer [30][31][32]. Our functional assays demonstrated that TIE1 promoted cervical cancer growth and metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…We found that TIE1 was upregulated in human cervical cancer and correlated with a poor prognosis. Consistent with our results, it has been indicated that elevated TIE1 expression is associated with a poor prognosis in patients with gastric cancer, ovarian cancer and metastatic breast cancer [30][31][32]. Our functional assays demonstrated that TIE1 promoted cervical cancer growth and metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…The ER acts as the specific cellular site of synthesis, folding, and structural maturation and trafficking of secretory and cell-surface proteins, and recent evidence showed that impaired ER homeostasis contributed to reproductive physiology and pathology including implantation and placentation, pregnancy complications and preterm birth (Guzel et al 2017). It was reported that CLN8 interacts with protein phosphatase 2A (PP2A) in human fibroblasts (Adhikari et al 2019), and as a major intracellular serine/threonine phosphatase, PP2A regulates a number of signaling pathways, including the cyclins/CDKs pathways (Lin et al 2018, Pippa et al 2020). CCNB1, CCND1 and CCNE1 have been reported to be involved in human EnSCs proliferation (Das 2009), and in the present study, decreased expression levels of these three cyclins were observed in miR-3074-5p-overexpressed T-HESC.…”
Section: Discussionmentioning
confidence: 99%
“…Then, secondary antibody with horseradish peroxidase was added and diaminobenzidine solution was applied, which was followed by 20% hematoxylin. Finally, the IHC signals of these slices were analyzed and scored by two veteran pathologists according to these scoring criteria 57 .…”
Section: Ethics Statement Clinical and Animal Ethics In This Study Wa...mentioning
confidence: 99%